2017
DOI: 10.5005/jp-journals-10003-1250
|View full text |Cite
|
Sign up to set email alerts
|

Anesthesia for Laser Surgery of the Airway

Abstract: Anesthesia for laser surgery carries a number of particular challenges and pitfalls. The airway is not only shared with the surgeon but also being operated upon. Personnel working inside the operating room must also be very aware of the benefits and dangers of medical lasers, and safety precautions must be taken to ensure their proper use. The anesthetist must have the knowledge and expertise to anesthetize a patient with a potentially compromised airway. This article deals with the anesthetic management of a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Studies with Nd:YAG laser has shown polyvinyl chloride, silicone and red rubber tubes to be vulnerable for damage because of ignition 4–7. Covering of tubes with laser safe material such as copper and aluminium foil is an option, but wrapping is to be done very carefully with a 30% overlap, with no exposed tube, and adhesive used to stick foil is also flammable 7. Commercially available laser-resistant tracheal tubes are expensive and their cuff is inflammable.…”
Section: Discussionmentioning
confidence: 99%
“…Studies with Nd:YAG laser has shown polyvinyl chloride, silicone and red rubber tubes to be vulnerable for damage because of ignition 4–7. Covering of tubes with laser safe material such as copper and aluminium foil is an option, but wrapping is to be done very carefully with a 30% overlap, with no exposed tube, and adhesive used to stick foil is also flammable 7. Commercially available laser-resistant tracheal tubes are expensive and their cuff is inflammable.…”
Section: Discussionmentioning
confidence: 99%